EFEKTIVITAS PEMBELAJARAN BERBASIS DISCOVERY LEARNING PADA MATERI KEGIATAN EKONOMI KELAS V DI SEKOLAH DASAR - Anggi Anggraini; Yasir Arafat; Susanti Faipri Selegi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effectiveness of the Discovery learning model on social studies learning of grade V students of SDN 79 Palembang. The samples in this study were VA class students as experimental research and VC class students as control classes. The number of samples in this study was 30 students in each class. The type of research used in this study is experimental research with the lecture method. Data collection techniques are carried out using tests, observation and documentation. The instrument used in the social studies learning test is in the form of a description test. Data analysis techniques using t-tests. The results of the hypothesis test then suggest that the sigmifikan (2-taileid) value is 0.000 because the significant value is more than 0.025, then H0 is rejected that means Ha is enmitted, so it can be implied that there is a moideil Eifeiktivity of Discoiveiry Leiarning learning in the mathematics of eikoinoimi activity in social studies teaching.